2009
DOI: 10.1111/j.1523-5378.2009.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness of the cagA Genotype in Children and Adults with Peptic Symptoms in South China

Abstract: cagA genotypes in children and in adults are different, and EPIYA-ABD may have potential clinical implication in the development of gastric cancer in South China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
5
11
0
Order By: Relevance
“…EPIYA motif types were all detected by PCR-based sequencing. Only 1 article [28] divided the population into adults and children. The detailed analysis of 1 EPIYA-D and 1 EPIYA-C motif and the total number of subjects is displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPIYA motif types were all detected by PCR-based sequencing. Only 1 article [28] divided the population into adults and children. The detailed analysis of 1 EPIYA-D and 1 EPIYA-C motif and the total number of subjects is displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, several studies have contradictory conclusions regarding the relationship between EPIYA-D and GC. For example, Li et al [28] found that H pylori strains carrying 1 EPIYA-D site are associated with increased GC risk. However, Xia et al [29] determined that 1 D site did not increase the risk of GC.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that the clinical strains used in the present study were isolated from children, thus leading to a more reliable model of the early natural conditions of the infection and one that is less influenced by environmental determinants. Several studies report that pediatric H. pylori strains display more distinct virulence profiles than those isolated from adults (13,18,25,34). Accordingly, the severity of H. pylori-associated disease in younger subjects may be closely related to the virulence of the strain, independently of the host factors, which may not be the case among adults.…”
Section: Discussionmentioning
confidence: 96%
“…According to different reports, either numbers or features of different motifs are changed by alteration of geographical locations, and their clinical outcomes are also affected by this variation. Western Asian isolates are therefore different from Eastern Asian isolates [11], and Eastern Asian isolates are more associated with gastric cancer than are Western isolates [72]. For example, studies by Zhou et al [37] and Chen et al [57] reported the prevalence of cagA among isolates associated with peptic ulcers and gastric cancers to be 100% and 94%, respectively.…”
Section: Discussionmentioning
confidence: 99%